Formación de ciudadanos con pensamiento crítico desde la enseñanza de las ingenierías. - Cano-Iglesias, María José; Franco-Mariscal, Antonio Joaquín (Aula Magna, 2023)
The development of critical thinking skills in citizens is a fundamental aspect in order to have reflective and critical citizens in the society in which they live. The development of these skills should be encouraged at all educational levels. The social issues where science and technology are involved become a good educational approach supported by some common strategies in the science and engineering edu cation, such as scientific practices of argumentation and inquiry, gamification, augmented reality or the use of audiovisual resources. This chapter offers a theoretical reflection, supported by evidence, showing the importance of the development of these skills in engineering education, since it is a professional activity with direct repercussions on society. The work covers the development of critical thinking through social issues such as the implementation of a nuclear power plant near a town, the choice of purchasing an everyday utensil, the role of women in science and technology, occupational hazards at work or the impact of a meteorite on Earth.
Copyright: Aula Magna/eds. lits.
Keywords: Ingeniería - Estudio y enseñanza superior; Pensamiento crítico; Argumentación; Toma de decisiones; Problemas sociocientíficos; Análisis crítico de la información